PENGARUH MODEL CIRC TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SEKOLAH DASAR - Sari, Siska Winda; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to analyze the effect of the application Cooperative Integrated Reading and Composition technique on the reading comprehension skills of the fifth-grade students of public Elementary school 54 Pontianak Barat. The method used in this research was an experiment with Quasi Experimental designed in the form of Nonequivalent Control Group Design. The population in this study was 71 fifth grade students. Data collection techniques used in this research were a measurement in the form of essay test questions. Based on the data analysis, the results of the experimental class showed that the average of post-test was 76.22 and the control class post-test was 70.01 with the results of tstat 3.019 > tcritical 1.669. Because tstat 3.019 > tcritical 1.669, then Ha was accepted. So, it concluded that there was an influence of the cooperative integrated reading and composition application on the reading comprehension skills of students. Based on the results of the calculation of the effect size (ES) which obtain ES 0.51, including medium category, that is 0,2> ES 0,8. This showed that the application of the cooperative learning model of integrated reading and composition provided a reasonably good influence on reading comprehension skills. Keywords: Cooperative Integrated Reading and Composition Technique, Influence, Reading Comprehension Skills